Comprehensive analysis of Arabidopsis expression level polymorphisms with simple inheritance - Stephanie Plantegenet; Johann Weber; Darlene R Goldstein; Georg Zeller; Cindy Nussbaumer; Jérôme Thomas; Detlef Weigel; Keith Harshman; Christian S Hardtke (Molecular Systems Biology)
Abstract In Arabidopsis thaliana, gene expression level polymorphisms (ELPs) between natural accessions that exhibit simple, single locus inheritance are promising quantitative trait locus (QTL) candidates to explain phenotypic variability. It is assumed that such ELPs overwhelmingly represent regulatory element polymorphisms. However, comprehensive genome‐wide analyses linking expression level, regulatory sequence and gene structure variation are missing, preventing definite verification of this assumption. Here, we analyzed ELPs observed between the Eil‐0 and Lc‐0 accessions. Compared with non‐variable controls, 5′ regulatory sequence variation in the corresponding genes is indeed increased. However, ∼42% of all the ELP genes also carry major transcription unit deletions in one parent as revealed by genome tiling arrays, representing a >4‐fold enrichment over controls. Within the subset of ELPs with simple inheritance, this proportion is even higher and deletions are generally more severe. Similar results were obtained from analyses of the Bay‐0 and Sha accessions, using alternative technical approaches. Collectively, our results suggest that drastic structural changes are a major cause for ELPs with simple inheritance, corroborating experimentally observed indel preponderance in cloned Arabidopsis QTL.